Analysis of urban surfaces to identify heat islands through the application of radiometric indexes and surface temperature - Silveira, Paula Carvalho da (2023)
The phenomenon called Heat Islands began to be noticed after the 19th century due to the great changes in the interactions of man with the surface. Studies related to climatology with the geotechnological advance were improved, which allows the analysis of different areas through the use of different methods. Thus, the objective of this study is to identify urban heat islands through remote sensing techniques, in different locations in the state of Santa Catarina: Joinville, Criciúma and Lages. For a better understanding of the urban surfaces of these cities, the following radiometric indexes were used: Normalized Density Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI) and Built-up Index (BU), in addition to Surface Temperature. Through the analysis of the results obtained, it was identified that heat islands are formed in areas that present high values ​​of BU and reduced values ​​of NDVI. The islands formed in Joinville and Criciúma occurred in a similar way, in the central portion of the cities due to the high density of urban elements, while in the city of Lages, the phenomenon was also concentrated in fragments of exposed soil, far from the urban area, due to the predominance of agriculture and forestry.